Does Debt Have Threshold Effects on Medium-Term Growth? Evidence from European Union Countries - Fir, Nejc (Naše gospodarstvo/Our economy, 2022)
Debt has become an important factor in economic activity and its extent has incentivized many researchers to incorporate it into contemporary growth models. On the positive side, debt has the ability to smoothen private consumption, firms’ investment and government expenditure in relation to their corresponding income, subsequently leading to better capital allocation. However, the history of debt defaults and lessons from European sovereign debt crises, which were accompanied by strict austerity measures, have warned us about the danger of debt overhang and unsustainable debt burdens. This paper tackles the question of the existence of a turning point, at which the negative effects of debt start to prevail in the economic process. In the sample of European Union countries in the period from 1995 to 2019, the author of this paper investigated the presence of threshold effects of government, non-financial corporate and household debt on medium-term growth following the paper by Mika and Žumer (2017). The author first confirmed the concave-shaped relationship between public debt and growth with a threshold of 111.6% of GDP, based on Eurostat debt-to-GDP data. In contrast, private debt was found to have first lag effects with an accompanied convex-shaped relationship between private debt and growth and with a corresponding threshold of 149.8% of GDP. Next, the author divided private debt into non-financial corporate and household debt to investigate a more detailed relationship between debt and growth. Corresponding to the Global Debt Database, the concave-shaped relationship between public debt and growth was confirmed with a threshold of 104.8% of GDP. Both of the investigated types of private debt confirmed the previously explored lagged impact on medium-term growth and a convex-shaped relationship between non-financial corporate and household debt and growth. The threshold of non-financial corporate debt stands at 138.3% of GDP, while that for household debt is 145.1% of GDP. Considering the presence of thresholds may offer an important message to economic policymakers, as timely and suitable governance can lead to either higher economic growth or prevent adverse effects of excessive indebtedness.